TEST THE EFFECTIVENESS OF EXTRACT THE SKIN KULIM (Scorodocarpus borneensis Becc) AS REPELLENT ANTI-MOSQUITO - Rivo Muhammad Yundeya; Evi Sribudiani; Sonia Somadona (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2023)
The use of Scorodocarpus borneensis Becc as wood causes its availability in nature to decrease. An alternative step to utilize and maintain the availability of Kulim in nature is to utilize Scorodocarpus borneensis Becc’s bark extract. The bioactive substances and scent of Scorodocarpus borneensis Becc are considered capable of repelling insects and replacing DEET in chemical mosquito repellent raw materials. The use of Kulim wood extract is considered to be far better than the use of chemicals that can affect human health. This research was conducted in three laboratories, namely the forestry laboratory, organic chemistry laboratory and natural synthesis and chemical engineering laboratory. The parameters to know the quality of the extract from the bark of the Scorodocarpus borneensis Becc’s branch were yield observation, color observation, odor test and skin sensitivity, phytochemical test and the extract effectiveness test against mosquitoes which were expected to be in accordance with the criteria of the pesticide commission of the Department of Agriculture in 1995. The results showed that the yield from Scorodocarpus borneensis Becc’s wood extract was found to be worth 0.83%, the color of the extract was brown because it used water solvent, the distinctive aroma of the Scorodocarpus borneensis Becc was not found in the extract because it was dominated by tannins and the extract felt warm on the skin, phytochemical tests showed that the kulim extract contained substances such as saponins, phenolic, steroids and tannins as well as the effectiveness test of the extract against mosquitoes found a protection result of 44% which has not been able to meet the standard of repellent protection criteria from the Pesticide Commission of the Department of Agriculture in 1995.